Party funding regulation in Poland (1990–2015): an appraisal - Bértoa, Fernando Casal (Politologia, 2018)
In the second half of 2015 Poland held a referendum in which voters were asked to give their opinion on the way party funding was regulated. Of those 7.8 percent of voters who turned out at the polls, only 17.4 percent voted in favour of the system of public funding in force at the time. Taking into consideration such a “negative” social opinion regarding the Polish regime of party funding, this article examines how political party funding (both public and private) is regulated in Poland, how it has changed over time, and how it could be developed. The main conclusion is that even if the current regime is better than the one existing before 2001, there is still much room for improvement.